Integrating Self-Determination Theory into Problem-Based Learning: A Systematic Review of Motivational Processes in Higher Education - Nurhartanto, Adhi; Sunyono, Sunyono; Maulina, Dina (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
Problem-Based Learning (PBL) has been widely adopted in higher education to promote active learning, clinical reasoning, collaboration, and self-directed learning; however, its motivational effectiveness remains inconsistent when students' psychological needs are not explicitly addressed in instructional design. This study aims to systematically review and synthesize the integration of Self-Determination Theory (SDT) within PBL environments to explain how autonomy, competence, and relatedness support motivation and meaningful engagement. Using a Systematic Literature Review guided by the PRISMA framework, peer-reviewed articles published between 2015 and 2025 were retrieved from the Scopus database. From 162 initially identified records, 18 articles met the inclusion criteria and were analyzed through thematic synthesis supported by bibliometric visualization using VOSviewer. The findings demonstrate that PBL is most effective when its instructional design intentionally supports students' three basic psychological needs. Autonomy is fostered through self-directed inquiry and meaningful learning choices; competence is developed through authentic problems, scaffolding, and formative feedback; and relatedness is cultivated through collaborative interaction and psychologically safe learning communities. However, integrated conceptual models linking PBL design, SDT mechanisms, and sustainable learning outcomes remain limited. This review contributes an integrative framework positioning SDT as an explanatory bridge between PBL instructional design and motivational outcomes, implying that lecturers and curriculum designers should conceptualize PBL as a motivational learning ecosystem rather than a mere problem-solving technique.